Biomass to hydrogen: A short biomass potential availability and conversion survey for Dutch municipalities - Rob Bastiaans (Open Journal of Environmental Biology - Peertechz Publications, 2023)
The local availability of lignocellulosic biomass was estimated for an arbitrary but representative Dutch municipality to facilitate the conversion and use of hydrogen on a decentralized scale. This study reveals that there is a large potential for this biomass at many locations to play important roles in the energy transition. It is meant as a call to the scientific community to activate individuals and get some inspiration.